Impact of targeted chemistries on maraging steel precipitation evolution observed using SANS and APT - Karen Perkins (Materials Characterization, 2018)
Building on a previous study of the novel aerospace maraging steel known as F1E, SANS and atom probe tomography (APT) have been used to study three variant chemistries designed to impact the growth and development of either laves or β-phase precipitates. One chemistry reduced the available laves forming elements, Mo and W, resulting in a reduction in both austenitization and aging laves populations. A second chemistry reduced the β-phase forming element, Al, causing a reduction in the nucleating laves but not β-phase precipitates. Mechanical properties such as tensile, creep and hardness are examined with respect to the precipitate populations.